Planning According to New Urbanism: the Ostadsara Neighborhood Case Study - Zali, Nader; Gholami, Nasim; Karimiazeri, Amir Reza; Azadeh, Seyed Reza (TeMA - Journal of Land Use, Mobility and Environment, 2016)
The modern urbanism activities have led to rupture of previous spatial structure of neighborhoods and destruction of their identity. The New Urbanism Movement, as one of the successful models in urbanization field attempts to revive this lost national-social identity through the project of returning to traditional structure of neighborhoods by applying modern urbanization models and methods. The current paper aims at evaluation and analysis of “the Ostadsara neighborhood’s organization based on new urbanism principles” and representation of solutions for planning a successful neighborhood center considering these principles. In this regard, various methods including library method, observation, photography, questionnaire and interview with users of the environment were utilized. The results from identification and assessment of weaknesses and strengths and specification and analysis of potential threats and opportunities shows the possibility of applying walkability, connectivity and integration, improvement of public transportation, improvement of architecture quality and urban design, maintenance and improvement of public and green open spaces, maintenance and strengthening the structure of traditional neighborhood units and using cooperation of Ostadsara neighborhood’s inhabitants. Finally, the current study will represent appropriate strategies for changing the mentioned neighborhood into a desirable and prosperous one.